Design of an Isolated Driver Module for Converters with Floating Transistors - González Marino, Gerónimo (2024)
This paper details the design and prototyping of a module for driving floating switching transistors. The module is developed to drive the power switches in multilevel or multi-transistor converters that require independent switching functions and have non-common terminals. The module consists of an isolated DC-DC converter that supplies power to the output stage of an opto-driver. Key design considerations, including the power requirements and the main aspects of the design of the power supply are discussed, as well as its isolated closed-loop compensation.